2006
DOI: 10.4314/ajbr.v8i1.35757
|View full text |Cite
|
Sign up to set email alerts
|

Weight changes and organ pathology in rats given edible larvae of <I>Cirina Forda</I> (Westwood)

Abstract: The effects of oral administration of extracts of raw and processed larvae of Cirina forda (Westwood) on morphometry and histo pathology were studied in albino rats. Weights of rats in the control group and in the group that were fed the processed larvae were significantly higher (p<0.05) than those of the group that received raw extract of the larvae. The relative weights of liver, heart, thyroid, pancreas and spleen were similar (p>0.05) in all the groups. The relative weight of lungs was significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Nigeria, Akinnawo et al (2002Akinnawo et al ( , 2005 showed that boiling and sun-drying of C. forda larvae reduced heart and liver toxicity in albino rats, while thorough heat treatment of Anaphe venata pupae was claimed to deactivate thiaminase activity (Nishimune et al 2000). There remains, however, a need to understand the inherent properties that confer on insects the ability to cause intoxication, the respective tolerance levels, and how processing may help in detoxification.…”
Section: Some Processing Procedures Have Been Shown To Lower Toxicitymentioning
confidence: 99%
“…Nigeria, Akinnawo et al (2002Akinnawo et al ( , 2005 showed that boiling and sun-drying of C. forda larvae reduced heart and liver toxicity in albino rats, while thorough heat treatment of Anaphe venata pupae was claimed to deactivate thiaminase activity (Nishimune et al 2000). There remains, however, a need to understand the inherent properties that confer on insects the ability to cause intoxication, the respective tolerance levels, and how processing may help in detoxification.…”
Section: Some Processing Procedures Have Been Shown To Lower Toxicitymentioning
confidence: 99%
“…18 The high crude fibre content in the insects could be due to the chitin normally found in insects. 2 Chitin is a structural nitrogen-based carbohydrate found in the exoskeleton of insects, which may have 'anti-nutrient' properties due to potential negative effects on protein digestibility. 5 A study comparing dried honey bees and honey bee protein concluded that the removal of chitin improved the quality of the insect protein as measured through protein digestibility, amino acid content, protein efficiency ratio and net protein utilisation.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of caterpillars is seasonal, and their supply and marketing have attracted the attention of several researchers. The cities of Ibadan [36,37], Abidjan [38], Yaoundé [39], Lubumbashi [40,41], Harare [42], Brazzaville [43], Kisangani [20], Bangui [44], Ilorin [45], Ndola [46], Kikwit [47], are good examples. These results support the findings of this study, which show that edible insect supply areas in urban areas (in the case of Kinshasa) are predominantly the nearby forest localities and a small proportion in the peripheries of these cities.…”
Section: Entomophagic Monodominance: the Case Of C Forda In Kinshasamentioning
confidence: 99%